2021
DOI: 10.1021/acs.jpcb.1c04766
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Proton Transport Mechanism for Uncoupling Proteins

Abstract: It has been suggested that uncoupling proteins (UCPs) transport protons via interconversion between two conformational states: one in the "cytoplasmic state" and the other in the "matrix state". Matrix and cytoplasmic salt-bridge networks are key controllers of these states. This study proposes a mechanism for proton transport in tetrameric UCP2, with focus on the role of the matrix network. Eleven mutants were prepared to disrupt (K → Q or D → N mutations) or alter (K → D and D → K mutations) the salt-bridges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
(228 reference statements)
0
10
0
Order By: Relevance
“…The difference between the m-gate networks with and without presence of CATR was also highlighted in earlier MD simulation studies on AAC [ 13 , 19 ]. A recent study on the uncoupling protein UCP2 also demonstrated the engagement of the three triplet 79 residues (R88, R185 and R279) in the broad matrix network [ 20 ]. Therefore, results from different groups consistently suggest that these non-motif basic residues are integral part of the broad matrix network.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the m-gate networks with and without presence of CATR was also highlighted in earlier MD simulation studies on AAC [ 13 , 19 ]. A recent study on the uncoupling protein UCP2 also demonstrated the engagement of the three triplet 79 residues (R88, R185 and R279) in the broad matrix network [ 20 ]. Therefore, results from different groups consistently suggest that these non-motif basic residues are integral part of the broad matrix network.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutagenetic and functional analysis of UCPs by different researchers and different methods provide important insights about fatty acid-UCP interactions, as well as residues that are involved in UCP-mediated transport. Table 1 shows the residues that are involved in proton transport regulation along with the major findings of related studies [4,28,53,59,60,[62][63][64][65][66][67][68]. It is widely accepted that proton flux by UCPs is activated by fatty acids [28,61].…”
Section: Regulated Proton Transport Across the Imm Is Facilitated By ...mentioning
confidence: 99%
“…All four proposed fatty-acid-mediated transport models involve mechanisms of proton transport through monomeric units of UCPs. Recently, a more complex Biphasic Two-State molecular model has been proposed for proton transport through oligomeric states of UCPs [55,68]. This model is based on a thorough comparative structural and functional analysis of tetrameric UCP2 and several mutants in model lipid bilayers [55,68].…”
Section: Regulated Proton Transport Across the Imm Is Facilitated By ...mentioning
confidence: 99%
See 2 more Smart Citations